PENINGKATAN PRODUKTIFITAS PADA UNIT PRODUKSI GULA SAGU UP2K SUNGAI TOHOR MELALUI PENERAPAN TEKNIK PENGERINGAN DENGAN CABINATE DRYER SAGO SUGAR - Hafidawati Hafidawati; Bagus Duhan Irfandy; Muhammad Agung Islamy; Muhammad Zahran Zaidan; Septy Khairany (Universitas Trisakti, 2022)
Sungai Tohor Village is located in East Tebing Tinggi District, Meranti Islands Regency, Riau Province which has great potential in the field of processing sago plants. In Sungai Tohor Village, there is a Family Income Improvement Business unit (UP2K) which has produced and marketed processed sago palm products in the form of sago sugar. Sago sugar has more advantages compared to other types of sugar besides its relatively cheap price, this sugar also has a low glycemic level making it suitable for people with diabetes. However, high market demand with low production capacity makes it difficult for sago sugar to meet the target. These problems arise because the production time of sago sugar is quite long around 4-5 days, this is due to the traditional drying of sugar because there is no technology that can be used in drying sago sugar effectively and efficiently. The purpose of this activity is to transfer knowledge and assistance in the process of drying the product. The method used is training and practice by the PKM-PI team at the University of Riau regarding the use of drying technology with the Cabinet Dryer Sago Sugar (CADESAR) drying device. Drying technology using CADESAR can improve the quantity and quality of sago sugar products. This technology can reduce production time by using a pressurized hot steam drying system, as one of the drying methods in the modern sugar industry, so that it can increase the amount of production and be more hygienic. The results of the training show that UP2K members can understand and practice knowledge of drying technology well. It is hoped that this will increase the productivity of their sago sugar business.